Evaluation of Mortality During Long-Term Treatment with Tafamidis for Transthyretin Amyloidosis with Polyneuropathy: Clinical Trial Results up to 8.5 Years - Merlini, Giampaolo (2022)
Introduction: The effects of tafamidis on mortality in Val30Met and non-Val30Met patients with transthyretin amyloidosis with polyneuropathy (ATTR-PN) were evaluated. Methods: The analyses were based on cumulative data from the Val30Met patients in the 18-month double-blind registration study and its 12-month open-label extension study, the non-Val30Met patients of the 12-month open-label study, and both patient groups in the ongoing 10-year extension study. Kaplan-Meier analyses of time to death from first treatment dose were performed. For the Val30Met group, two treatment groups were analyzed: those who received tafamidis in both the parent and extension studies (T-T) and those who received placebo in the parent study and switched to tafamidis in the extension studies (P-T). Results: Kaplan-Meier estimates (95% confidence interval [CI]) were available up to 9 years for the Val30Met group, at which time 85.9% (53.1-96.4) and 91.1% (77.9-96.6) of the patients in the T-T and P-T groups, respectively, were alive. For the non-Val30Met group, estimates were available up to 8 years from the first dose, and the percentage of patients alive was 75.9% (47.7-90.2). Conclusion: Long-term tafamidis treatment may confer survival benefit in patients with ATTR-PN.